Antidepressant-like activity of the dipeptide mimetic of brain-derived neurotrophic factor GSB-106 in Porsolt test after intraperitoneal sub-chronically and chronically treatment in mice - A. V. Tallerova; P. Y. Povarnina; S. V. Minaev; T. A. Gudasheva; S. B. Seredenin (LLC "Publisher OKI", 2020)
The present work was to study the GSB-106 effect on the immobility behavior of mice Balb/c in the Porsolt test. GSB-106 was administered sub-chronically and chronically intraperitoneal in dose 1 mg/kg. GSB-106 administration significantly decreased immobility time in mice by 1.2 times after 4 days, by 1.3 times after 14 days and 1.2 times after 21 days' injections. Thus, the dependence of the GSB-106 effect-time administration in the Porsolt test was not established.